2021
DOI: 10.1186/s41072-021-00091-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Panama Canal expansion on Latin American and Caribbean ports: difference in difference (DID) method

Abstract: The expanded Panama Canal opened on June 26, 2016. This expansion is the third set of locks that enabled the canal to double its capacity through the addition of new traffic lanes, which allowed neo-Panamax and some post-Panamax vessels to transit across the canal. The widening of the canal has increased maritime traffic within Latin America and the Caribbean (LAC). Major ports in the regions have made huge investments in port expansion and infrastructural development to accommodate neo-Panamax vessels. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 34 publications
0
0
0
1
Order By: Relevance
“…On the contrary, the results of this research contradict the estimates by the U.S. Department of Transportation and Maritime Administration (2013), Serebrisky et al (2016), andPagano et al (2016), who forecasted that the Panama Canal expansion would increase port preference, boost challenges, and enhance the competitiveness of its maritime cluster, respectively. Additionally, the results partially contradict estimates that the Panama Canal expansion would increase port container throughput in the Central America region (Miller & Hyodo, 2021).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…On the contrary, the results of this research contradict the estimates by the U.S. Department of Transportation and Maritime Administration (2013), Serebrisky et al (2016), andPagano et al (2016), who forecasted that the Panama Canal expansion would increase port preference, boost challenges, and enhance the competitiveness of its maritime cluster, respectively. Additionally, the results partially contradict estimates that the Panama Canal expansion would increase port container throughput in the Central America region (Miller & Hyodo, 2021).…”
Section: Discussioncontrasting
confidence: 67%
“…Likewise, a study concluded that the expanded Panama Canal would produce a smaller impact on the cargo competition for ports located in Europe than those located in the United States given their longer geographical distance from the canal (Hassel et al, 2020). Additionally, Miller and Hyodo (2021) conducted a study on 100 ports on the Latin American and Caribbean sides of the canal and concluded that the Panama Canal expansion had significantly increased cargo volume in Latin American ports, except for some ports in the Caribbean region.…”
Section: Literature Review the Panama Canal Expansionmentioning
confidence: 99%
“…PRIMER: PANAMSKI PREKOP [17] Razširitev Panamskega prekopa, ki je bila dokončana v letu 2016, predstavlja enega od največjih inženirskih dosežkov v zgodovini prometa in logistike. Projekt je vključeval izgradnjo novih zapornih komor in širitev kanala, imenovanega »Neo-Panamax«, ki omogoča prehod večjim ladjam.…”
Section: Prometni Izziviunclassified
“…In addition, an estimated 20 percent of the government's revenue comes from Canal activity (direct, indirect, and induced). The expansion also allowed transport companies to consolidate cargo in fewer vessels, thus reducing fuel costs and carbon emissions (Miller and Hyodo, 2021). For example, doubling the maximum container ship size has reduced total vessel cost per transported container by roughly a third over the last decade (Merk, 2018).…”
Section: Box 32 -Transformational Projects Supported By Idb Investmentioning
confidence: 99%